NILAI-NILAI PENDIDIKAN AKHLAK DALAM KITAB AL-ĀDĀB AL-‘ASYARAH KARYA ṢĀLIḤ IBN ‘ABDILLĀH AL-‘UṢAIMĪ DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Latif, Attabik Ahmad; Fahamsyah, Fadlan (LPPM UM Metro, 2024)
This research is motivated by the moral decline that is commonly found in Indonesia, especially in the world of education. This research aims to: (a) know the values of moral education in the book of al-Ādāb al-‘Asyarah by Ṣāliḥ Ibn ‘Abdillāh al-‘Uṣaimī, (b) know the relevance of moral education values in the book of al-Ādāb al-‘Asyarah by Ṣāliḥ Ibn ‘Abdillāh al-‘Uṣaimī with Islamic Religious Education. This thesis includes qualitative research. This study is using documentation. The object of this study is the Book al-Ādāb al-‘Asyarah by Ṣāliḥ Ibn ‘Abdillāh al-‘Uṣaimī. The collected data were analyzed using content analysis. The findings of this research that includes: 1) The moral education values contained in this book can be classified into three categories: First, Moral Education Values to Allah, namely (a) Praying to Allah, and (b) Remembering Allah. Second, the value of moral education to fellow humans, namely (a) saying and replying to greetings, (b) asking permission before entering other people's homes, (c) eating the closest food when with other people, (d) speaking kindly and politely, (e) not disturbing other people with sneezing sounds, (f) not disturbing other people with smoking sounds, and (g) praying for goodness for others. Third, the value of moral education to oneself, namely (a) morals towards Jasadiyyah (physical and bodily) which includes (1) dressing beautifully, (2) sitting in a quiet place, and (3) licking the remaining food on the fingers after eating, and (b) morals towards Nafsiyyah (soul and intellect) which includes (1) lowering the gaze, and (2) ablution before bed. 2) The relevance between the values of moral education contained in the book of al-Ādāb al-‘Asyarah with Islamic Religious Education is the suitability between the existing material in the form of moral education with the provisions and arguments in Islam.Keywords: Moral Education, al-Ādāb al-‘Asyarah, Islamic Education